Analisis Konseptual Tata Kelola dan Tindak Lanjut Pengelolaan Pondok Pesantren Bani Huzaifah dalam Meningkatkan Transparansi dan Akuntabilitas - Annisa Annisa; Nur Aznisyah; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
This study conceptually examines the governance and follow-up management of the Bani Huzaifah Islamic Boarding School in order to strengthen the transparency and accountability of the institution, given the increasing public demand for information disclosure and administrative order in religious educational institutions. The approach used is descriptive qualitative based on literature study, with data sources in the form of regulations from the Ministry of Religious Affairs, pesantren institutional documents, and previous studies related to pesantren management, good governance, internal audit, and public accountability. The results of the study show that many Islamic boarding schools, including Bani Huzaifah, still face challenges in the form of simple financial records, limited administrative human resources, minimal use of technology, and weak documentation and follow-up monitoring mechanisms. The discussion emphasizes the importance of strengthening organizational structures, developing SOPs, implementing digital systems, and conducting continuous audits balanced with stakeholder involvement. This study concludes that modern, documented, and value-based pesantren governance is a key prerequisite for transparency and accountability, which can enhance public legitimacy and institutional sustainability.